Dietary inclusion of chestnut (Castanea sativa) polyphenols to Nile tilapia reared in biofloc technology: Impacts on growth, immunity, and disease resistance against Streptococcus agalactiae - Van Doan, Hien; Hoseinifar, Seyed Hossein; Hung, Tran Quang; Lumsangkul, Chompunut; Jaturasitha, Sanchai; Ehab El-Haroun; Paolucci, Marina (Fish & shellfish immunology, 2020)
A feeding trial was carried out to examine the effects of adding chestnut (Castanea sativa) polyphenols (CSP) on the growth, skin mucus and serum immune parameters of Nile tilapia (Oreochromis niloticus). Five experimental diets with inclusion levels of 0, 1, 2, 4, and 8 g kg-1 of CSP were fed to Nile tilapia fingerlings (12.77 ± 0.17 g fish-1) during an eight-week trial. Fish were analyzed on the fourth and eighth week to determine the influences of CSP on growth, skin mucus, and serum immune parameters. Challenging test versus Streptococcus agalactiae was evaluated at the end of the trial. Fish fed with CSP enriched diets displayed a significant increase (P ≤ 0.05) in growth and a decline in feed conversion ratio (P ≤ 0.05). Similarly, skin mucus and serum immune parameters were significantly increased (P ≤ 0.05) in fish fed CSP with respect to the control. The effects were already evident four weeks after the CSP administration. The disease protection test displayed that the fish's survival rate was significantly higher (P < 0.05) in CSP diets over the control. The relative percentage of survival (RSP) was 62.5, 75.0, 58.3, and 37.5 in fish fed diets contained 1, 2, 4, and 8 g kg-1 CSP, respectively. The best effect on growth, immune response, and disease resistance were shown in Nile tilapia fed with a diet supplementation of 2 g kg-1 CSP.
Keywords: Animals; Biofloc system; vztah mezi dávkou a účinkem léčiva; cichlidy; Fagaceae; streptokokové infekce; Animal Feed; Polyphenols; Dietary Supplements; odolnost vůči nemocem; Disease Resistance; nemoci ryb; Chestnut polyphenols; Fish Diseases; Nile tilapia; Streptococcus agalactiae; Disease resistance; potravní doplňky; Growth performance; dieta; Cichlids; Dose-Response Relationship, Drug; Diet; Streptococcal Infections; krmivo pro zvířata; polyfenoly; Random Allocation; zvířata; Innate immunity; náhodné rozdělení